Knowing brown and inventing green? Incremental and radical innovative activities in the automotive sector - Julia Mazzei; Tommaso Rughi; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
The development of low emission vehicles (LEVs) in the automotive sector stands out in the literature as a typical case of technological competition between a dominant design and a set of alternative green technologies. The incremental trajectory of green technologies aimed at improving the efficiency of the internal combustion engine (ICEG) is competing with a radical trajectory targeted to the development of hybrid, electric and fuel cell vehicles (HEF). Exploiting a novel dataset of firm- and patent-level information retrieved from ORBIS-IP and containing USPTO patent applications between 2001 and 2018 in the automotive sector, we first cluster firms according to their relative patent share and degree of specialization in each trajectory, identifying a technological landscape in which they locate with distinct strategies. We then investigate the extent to which different stocks and combinations of knowledge might explain such heterogeneity in innovative efforts and positioning in the landscape. Our results suggest that a stock of ''brown'' knowledge closely related to ''green'' knowledge proves to be valuable for firm's success in each trajectory. Moreover, firms with a broad array of different knowledge sources are capable of reaching a leadership position in the technological landscape.
Keywords: O33; O34; Q55; L62; 330; Low emission vehicles; relatedness; diversification; knowledge